Material Properties and Microstructures of Electron Beam Welding Similar and Dissimilar Titanium Alloys - Mitchell, Ryan James (Auckland University of Technology, 2011)
Titanium is considered one of the best engineering materials for industrial applications with the different alloys offering a range of properties, which include low density, high fatigue life, corrosion resistance and high strength. Electron beam welding (EBW) is a high energy density welding process that occurs in an inert high vacuum environment. Welding of dissimilar metals or alloys offers the opportunity to take advantage of different material properties in different areas of a single part. The research aim of this master’s project was to identify the properties and microstructure of electron beam welding similar and dissimilar titanium alloys. Similar and dissimilar titanium alloy butt joint welds were created using an electron beam process. The welds consisted of commercially pure titanium (CP Ti), α+β alloy Ti6Al4V (Ti64) and β alloy Ti5Al5V5Mo3Cr (Ti5553). Microstructure was studied through the use of metallography and optical microscopy. Electron microprobe microanalysis (EPMA) was performed to identify the chemical composition across the welded samples. Mechanical testing was performed on welded samples to study the joint integrity and fracture characteristics. A scanning electron microscope investigation was performed on the fracture surface to reveal their fracture modes. Visually acceptable crack free electron beam welds were achieved for all similar and dissimilar combinations of titanium alloys. EPMA (electron microprobe microanalysis) scans showed that the dissimilar welds were well mixed with consistent composition across their fusion zones. Microhardness profiles of similarly welded CP Ti and Ti64 showed no significant change of the hardness in HAZ or fusion zones. Similarly welded Ti5553 alloy microhardness profiles showed softening in the HAZ and fusion zones. Dissimilar welds with Ti5553 showed a significant increase in hardness in the fusion zone. Most weldments exhibited mechanical properties comparable to the base metal, with negligible loss in ductility exhibited during tensile testing. Ti5553 to Ti64 and Ti5553 to Ti5553 weldments both failed prematurely below the tensile strength of both materials and exhibited very little elongation. Porosity was observed in the Ti5553 to Ti64 fusion zone. Early investigation using the Aramis system showed some confidence of significant elongation occurring in the fusion zones of similar and dissimilarly electron beam welded Ti5553.
Keywords: Titanium; Dissimilar welding; Ti5553; Electron Beam welding; EBW; Titanium alloys